Parents' Knowledge and Attitudes When Choosing Their Children's School Bag: an Introductory Study - Laštro, Dijana; Muftić, Mirsad; Ponorac, Nenad; Bokonjić, Dubravko (Scripta Medica, 2021)
Background/Aim: A school bag is a device whose purpose is to store things that are necessary for a child in performing daily productive activities. The aim of the research was to examine how much parents are informed about the school bag and which specifications are crucial when choosing a school bag for their children.Material and methods: The prospective study included 150 parents of students aged 11 to 12 from Banja Luka. For the purposes of the research, a questionnaire with closed and open questions was used. Results: More than 97 % of the surveyed parents belonged to the age range of 30 to 49 years. The largest number of surveyed parents have had secondary education 44 %, but the number of university-educated parents was also very high 39.3 %. Ninety-six percent of students used a backpack. School bags in 97.4 % of cases were purchased in stores. Only in 10 % of cases, school bags fully meet the basic criteria. In the remaining 90 % of cases, there was an absence of at least one or more desired characteristics. Using the Chi-squared test (χ2 = 245.45; p < 0.001), a significant difference between the desired and the achieved result was statistically proven. 77.3 % of parents did not receive information about the school bag. Salespeople (11.3 %), other parents and friends (9.3 %) were the main source of information before purchasing a school bag. In the future, 54 % of parents would like to get information about the school bag through lectures and practical workshops for children and parents. Conclusion: Greater information enables adequate selection and reduces the possibility of marketing tricks and influences on consumers when choosing the desired product such as a school bag. Parents have an important role to play in ensuring unhindered growth and development during the educational process and in raising children's awareness and supervision of the proper use of the school bag.
Keywords: Schoolbag; Parents; Knowledge; Awareness